2021
DOI: 10.1111/ijcp.14511
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of intravenous dexketoprofen and paracetamol in the management of pain induced by sore throat

Abstract: One of the most common reasons for emergency department (ED) admissions is sore throat, which is a prevalent clinical manifestation disturbing patients, especially with upper respiratory tract infections (URTI). Some patients with URTI present to ED with moderate to severe sore throat pain. 1 In such a case, the primary goal of treatment in ED is to alleviate pain immediately and maximising patient comfort with minimum side effects.Relieving sore throat pain in both acute and chronic periods is an indispensabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There was no significant difference between groups in terms of the mean DSS, SPIS, SwoTS, and STRS scores at the examined time points. Both drugs reduced the sore throat equally [17].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…There was no significant difference between groups in terms of the mean DSS, SPIS, SwoTS, and STRS scores at the examined time points. Both drugs reduced the sore throat equally [17].…”
Section: Resultsmentioning
confidence: 93%
“…Cimen U. et al compared intravenous DEX with paracetamol for the treatment of sore throat pain in a randomized, prospective, controlled, double-blind study [17]. Two hundred adult patients were enrolled in the study and divided into two groups.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective randomised controlled double-blind study investigating the efficacy of intravenous dexketoprofen and paracetamol in resolving pain caused by sore throat reported that both exhibited similar analgesic effects by reducing throat pain to a comparable extent. 26 However, German guidelines recommend ibuprofen or naproxen for symptomatic therapy in acute pharyngitis and only offer weak support for the use of throat preparations (pastilles, gargle solutions or sprays) containing local anaesthetics and/or non-steroidal anti-inflammatory drugs. 27 It should be remembered that the throat preparations prescribed as symptomatic therapy provide, at best, low effectiveness for a brief period against self-limiting symptoms.…”
Section: Implications For Research and Practicementioning
confidence: 99%